Ethics in the governance of telecommunications: accountability of global industrial actors - Katharine Sarikakis; Krisztina Rozgonyi (International Telecommunications Society (ITS), 2016)
Historically, the development of tele-communications has been at the heart of State policy based on a set of principles revolving around notions of modernisation, on the one hand, and nation-building, on the other. They were operationalized in State planning for domestic infrastructure, regulation of market, and communication control. Internationally, telecommunications constituted a core piece in the toolbox of foreign policy and international trade hegemony. The physical scarcity of resources and high costs (i.e. frequencies, cables) and the principles of placing the State at the centre of managing the telecoms and media landscapes have dominated the largest part of communications history. With the successive waves of a. liberalisation and b. technological change, the role of the State has receded and the role of international organisations and private actors has become paramount in setting not only the scene for the technological development in the sector, but importantly, in shaping the principles under which the sector is regulated on a day to day basis. Technological and societal changes shaped the functioning of the telecoms sector, which has become an interconnected ecosystem. Further, regulatory change, in terms of actors, principles and processes is shaping the everyday experience of citizens (or users) around the globe: the role of the global telecommunication industry in social and economic development is underpinned by an unprecedented growth over the past 15 years (ITU International Telecommunications Union, 2015a). This growth is strictly connected to access to spectrum and to the adoption of mobile broadband services (ITU; UNESCO, 2015), (GSMA GSM Association, 2016), one of the most valuable public goods globally (Samuelson, 1954), (Samuelson, 1955), (Holcombe, 1977). The future of communication services lies with the utilization of spectrum bands, and scarcity thereof is a matter of public policy about the utilization of public communicative spaces (Sarikakis, 2012); therefore public accountability (Bovens, Goodin, & Schillemans, 2014) by its `users', i.e. telecom operators is a legitimate expectation of global and local publics. An often ignored dimension of principles and practice of public accountability of corporations around transparency and integrity, as the new core actors in the global communications regime. Historic failures and structural weaknesses in emerging, developing and least developed countries on forced implementation of competition policies and introduction of `one-size-fits-all' legal and regulatory frameworks have systematically failed to address serious concerns regarding corruption and integrity structures and have paved the way to current corruption incidents worldwide (Chakravartty & Sarikakis, 2006; Sutherland, 2013). The demands of investors of industrialised countries dictated the implementation of historically and politically ungrounded policies and regulations with severe impacts to the accessibility and affordability of telecoms infrastructure in developing countries today, hence widening the digital divide. This paper explores the processes of governing spectrum and connects to accountability mechanisms of European telecom operators as key actors in providing an integrated infrastructure for global sharing of information with a significant impact to the global digital divide. We apply an analysis that takes into account multi-level, multi-actor, multi-purpose factors in the future of information infrastructure – to the increased role of spectrum management, to the effects and impact of globalization of actors and to the role of private sector actors in shaping communication (Sarikakis & Rodriguez-Amat, 2013). The paper surveys the ways in which policies about public accountability and integrity are exercised globally and explores possible connects to the governance of spectrum utilization. We argue that corporate actors bear social and political responsibilities as political actors in the process of governance and discuss the role of European policies in shaping and enforcing those responsibilites. We further elaborate possible regulatory frameworks in the context of social (power) relations (Bovens, Goodin, & Schillemans, 2014) and of empowered inclusion (Warren, 2004) in regards to integrity. We further argue for the need of supra-national regulation at EU-level to secure integrity in spectrum management. We recommend possible and necessary sector-wide initiatives to implement new standards fostering transparency in spectrum licensing, including a minimum set of criteria to be implemented within the licensing process.
Keywords: 330; global communication governance; accountability; integrity; policy principles